Communicative activities in improving english language proficiency among non-english major undergraduates in a public university, Malaysia - Abdul Kareem, Othman (2018)
This study examine the relationship of communicative activities and English language proficiency of non – English major programme undergraduates from various faculties at Universiti Putra Malaysia. 60 non - English programme undergraduates were selected based on their performance in a proficiency course and Malaysia University English Test (MUET) for this study. They were categorised into experiment and control groups. The experimental group will be exposed with several communicative activities while the controlled group has normal classroom lesson. This research employed pre- and posttests, questionnaires and interviews as its instruments for data collection. The duration of this study was for one semester. The significance of findings indicated that there are relationship between these communicative activities in improving undergraduates’ levels of English language proficiency. Impacts and implications of these findings are detailed in the discussion of this study.